Impact of mesoscale eddy parameterization on Arctic Atlantic Water circulation and heat transport in the eddy-permitting grey zone - Per Pemberton; Iréne Wåhlström; Sam T. Fredriksson (Ocean Science, 2026)
The Arctic Ocean is undergoing rapid change, yet many CMIP-type climate models struggle to accurately represent its circulation and water masses. A key feature of the system is the topographically controlled boundary currents that transport warm, saline Atlantic Water northward at intermediate depths into the Atlantic Water layer. An important process affecting these boundary currents is the lateral flux of heat and salt driven by mesoscale eddies. Because the deformation radius is relatively small in the Arctic Ocean, numerical simulations require kilometer-scale resolution to fully capture eddy dynamics. Most of the current climate models, however, operate in a non-eddying regime, relying on mesoscale eddy parameterizations – typically combining isopycnal diffusion (Redi) with eddy-induced advection (Gent and McWilliams, GM). As horizontal resolution increases, future models will shift from an eddy-parameterized to eddy-permitting regime, entering a grey zone where eddies are only partially resolved and the role of GM parameterization becomes less straightforward. This study investigates the use of GM parameterization in eddy-permitting models, focusing on its effect on the northward transport of Atlantic Water in the Nordic Seas and Arctic Ocean. We conduct realistic simulations where we vary GM diffusivity strength and test two different GM scalings. These experiments are compared with a high-resolution reference simulation and observational data. Further, we show how the GM parameterization modulates the topographically steered boundary current through a reduction in baroclinicity of the large-scale circulation, how transport across Greenland–Scotland Ridge and Fram Strait is controlled by its strength; and how resolved and parameterized eddy heat fluxes contribute to the redistribution of heat. Our results suggest that mesoscale eddy buoyancy fluxes remain insufficiently resolved at eddy-permitting Arctic resolutions, supporting the continued use of GM-type parameterizations in the grey-zone regime. However, there are some obvious limitations with the tested GM formulations in our experiments that warrants further improvement of the GM scheme in an Arctic context.

Submesoscale dynamics in the Baltic Sea – a review - Urmas Lips; Kai Salm; Germo Väli; Taavi Liblik; Lars Arneborg; Louise C. Biddle; Anna I. Bulczak; Evridiki Chrysagi; Małgorzata Falarz; Peter Holtermann; Jaromir Jakacki; H. E. Markus Meier; et al. (Progress in Oceanography, 2026)

Response of a semi-enclosed sea to perturbed freshwater and open ocean salinity forcing - Lars Arneborg; Magnus Hieronymus; Per Pemberton; Ye Liu; Sam T. Fredriksson (Ocean Science, 2026)
The sensitivity of Baltic Sea salinities to changed freshwater forcing and other forcing factors have been debated during the last decades, since changed salinities would have large impacts on the marine ecosystems, and since this parameter still shows a high degree of uncertainty in regional climate projections. In this study, we performed a sensitivity experiment where freshwater forcing and salinities at the outer boundaries of the North Sea were perturbed in a systematic way in order to obtain a second-order Taylor polynomial of the statistical steady state mean salinity. The polynomial was constructed based on perturbations of a 57 year long hindcast run for the period 1961–2017 with a regional ocean model covering the North Sea and the Baltic Sea. The results show that the Baltic Sea is highly sensitive to freshwater forcing, and that about one third of the boundary salinity change propagates into the Baltic Sea. The results are also analysed in terms of a total exchange flow analysis in the entrance region, and it is found that the Baltic Sea salinity sensitivity to freshwater forcing to a large degree can be explained by increased freshwater input causing (1) dilution inside the Baltic Sea, (2) decreased inflows caused by changes to the mean sea level gradient in the entrance region, and (3) reduced inflow salinities due to recirculation of outflowing Baltic Sea water in the entrance region where the inflow water consists of about two parts outflowing Baltic water and one part North Sea water. Besides providing new understanding of the processes that govern the Baltic Sea salinity sensitivity to freshwater forcing, the results of this study provide means of quickly assessing Baltic Sea salinity changes based on changes of North-East Atlantic salinities and Baltic Sea freshwater forcing.

Sensitivity of the overturning circulation of the Baltic Sea to climate change, a numerical experiment - Robinson Hordoir; Anders Höglund; Per Pemberton; Semjon Schimanke (Climate Dynamics, 2018)